Epidemiological profile of tuberculosis in the city of Belo Horizonte (MG), from 2002 to 2008 - Dener Carlos dos Reis; Thiara Amanda Corrêa de Almeida; Humberto Ferreira de Oliveira Quites; Mariana Mattar Sampaio (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
Objective: To assess the epidemiological profile of tuberculosis in Belo Horizonte, Minas Gerais State, from 2002 to 2008. Methods: For descriptive epidemiological study, the data were obtained from the municipal National Health Surveillance System, after obtaining approval from the Research Ethics Committee at the City Health Department. Incidence coefficient, average rates and stratified data analysis with significance level of p ≤ 0.05 were calculated. Results: About 7.590 new tuberculosis cases were reported between 2002 and 2008. There was a slight reduction in the number of cases throughout the historical trend, with an average annual incidence rate of 46/100,000 inhabitants. The study also showed a male gender ratio of 1.84:1, a higher incidence coefficient in the age group between 40 and 59 years old (73/100,000) and a higher incidence of tuberculosis among people who only had primary education level. Pulmonary tuberculosis was the most prevalent form in every year of the study (p < 0,001). Among the cases reported with associated diseases, alcoholism was registered in 47.9% and AIDS in 34.5%. Between 2002 and 2008, there was an increasing trend of cases treated under Directly Observed Treatment, accounting for 29.5% in total. Cure percentage rate was below the expected result (67.3%) and non-adherence to treatment showed a high total percentage (17.9%). Conclusion: The results indicated that tuberculosis control actions need to be intensified with investments on professional training, systemic audits of the information system, improved integration between AIDS/tuberculosis programs and raising awareness of the disease with the goal of mobilizing the society.